Using Photomath Applications on Student Learning Outcomes in Advanced Calculus Courses - Dewi, Ardiana Fatma; Ahadiyah, Kurnia (Proceeding International Conference on Education, 2023)
Along with the development of the times, the world of education is much influenced by advances, especially in the field of information and communication technology. Many educators use technology as a learning medium to help students learn and solve problems, especially math problems. There are several applications that students use to help them complete lecturer assignments. Photomath is one of the applications used by students in mathematics lessons. This application can be accessed via a smartphone and has features that help students solve math problems. This study aims to determine the effect of using the Photomath application on the learning outcomes of Tadris Mathematics students in semester 4 of the State Islamic Institute (IAIN) Kediri. The number of samples used in this study were 45 students, which were divided into two groups. The experimental group consisted of 24 students and the control group consisted of 21 students. The analysis used in this study is a t-test to compare whether there are differences in student learning outcomes in advanced calculus courses when solving problems using the Photomath application and not using these tools. The results obtained show that there are significant differences between students who use the help of the Photomath application and those who do not. So it can be concluded that the use of the Photomath application has an effect on student learning outcomes at IAIN Kediri's mathematics tadris in advanced calculus courses.